Lessons for Monetary Policy : What Should the Consensus Be? - Issing, Otmar (Washington, D.C. : International Monetary Fund, 2011)
This paper outlines important lessons for monetary policy. In particular, the role of inflation targeting, which was much acclaimed prior to the financial crisis and since then has not lost much of its endorsement, is critically reviewed. Ignoring the relation between monetary policy and asset prices, as is the case in this monetary policy approach, can lead to financial instability. In contrast, giving, inter alia, monetary factors a role in central banks' policy decisions, as is done in the ECB's encompassing approach, helps prevent these potentially harmful side effects and thus allows for fostering financial stability. Finally, this paper makes a case against increasing the central banks' inflation target.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet